The biological aspect of shark which landed in Karangsongs Port, Indramayu, West Java - Pramesti, Defta Ninggar; Khan, Alexander M.A; Dewanti, Lantun Paradhita; Ismail, Mochamad Rudyansyah (Universitas Malikussaleh, 2023)
This study aimed to evaluate the number of catches and describe the biological aspects of sharks landing at Karangsongs Port Indramayu, West Java. The study was conducted from July until August 2022 with the survey method. Data were taken by purposive sampling method including species, number of catches, sex, maturity level, total length, weight, fishing gear, and location. Data were analyzed to evaluate the catch while biological aspects were used to determine the condition of sharks. Analysis of biological aspects included sex ratio, length frequency, and the level of male sex maturity, as well as the length-weight relationship. A total of 407 sharks consisting of 7 species were dominated by mature sharks. Include Carcharinus dussumieri (33,2%), Carcharinus sorrah (23,8%), Carcharinus limbatus (0,2%), Sphyrna lewini (8,4%), Rhizoprionodon acutus (1,5%), Chiloscyllium punctatum (12,5%), Loxodon macrorhinus (8,4%). The results showed the frequency distribution of fish length and weight is 44 cm to 106 cm and 0,2 to 8,5 kg. Statistical test results showed that sharks had growth patterns negative allometric and Biological aspects showed an unbalanced sex ratio.Keywords: Allometric; Growth; Sex ratio; Shark